Clinical Research Progress of the Post-Stroke Upper Limb Motor Function Improvement via Transcutaneous Auricular Vagus Nerve Stimulation - Xiaolong Shi; Jingjun Zhao; Shutian Xu; Meng Ren; Yuwei Wu; Xixi Chen; Zhiqing Zhou; Songmei Chen; Yu Huang; Yuanli Li; Chunlei Shan (Neural Plasticity)
Stroke is a disease with high morbidity and disability, and motor impairment is a common sequela of stroke. Transcutaneous auricular vagus nerve stimulation (taVNS) is a type of non-invasive stimulation, which can effectively improve post-stroke motor dysfunction. This review discusses stimulation parameters, intervention timing, and the development of innovative devices for taVNS. We further summarize the application of taVNS in improving post-stroke upper limb motor function to further promote the clinical research and application of taVNS in the rehabilitation of post-stroke upper limb motor dysfunction.